2015
DOI: 10.12740/app/37943
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of post-traumatic stress disorder among women with normal vaginal delivery in Zahedan city

Abstract: Aim:The study aimed to determine the prevalence of post-traumatic stress disorder (PTSD) among postpartum women in Zahedan city, Iran. Method: Data in this cross-sectional study were gathered from healthcare centres of Zahedan, a city in south-east Iran. Four-hundred women with childbirth experience over the past few months were selected; between 6 and 24 weeks had passed since their delivery. We used three questionnaires in order to evaluate the demographic data, PTSD symptoms and traumatic childbirth experie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Limited to women between 18 and 35 years oldPrimiparasNormal10,05060.63.515.796.5Khaskheli et al (2012)Pakistan (2006–2010)Case series (Cross sectional data)Medical facility (hospital)All cases admitted in maternity ward. The study included all the women delivering in the hospital and all referred from outside either from local maternity homes, rural health centres and delivery at home within 40 daysMixedNS92160.6Khresheh et al (2009)Jordan (July–August 2004)Cross-sectionalMedical facility (hospital)All vaginal deliveries during study periodMixedMixed90554.30.4515.8Koettker et al (2012)Brazil 2005–2009Cross-sectionalHomeAll women with planned home birth (low risk pregnancies)MixedNS891.1Kongnyuy et al (2008)Cameroon (2004–2005)Cross-sectionalMedical facility (hospital)Singleton pregnancyPrimiparasMixed100311.6Saxena et al (2010)India (2007)CohortMedical facility (hospital)All vaginal deliveries during study periodPrimiparasMixed21067.60.95Moghadam et al (2015)…”
Section: Resultsmentioning
confidence: 99%
“…Limited to women between 18 and 35 years oldPrimiparasNormal10,05060.63.515.796.5Khaskheli et al (2012)Pakistan (2006–2010)Case series (Cross sectional data)Medical facility (hospital)All cases admitted in maternity ward. The study included all the women delivering in the hospital and all referred from outside either from local maternity homes, rural health centres and delivery at home within 40 daysMixedNS92160.6Khresheh et al (2009)Jordan (July–August 2004)Cross-sectionalMedical facility (hospital)All vaginal deliveries during study periodMixedMixed90554.30.4515.8Koettker et al (2012)Brazil 2005–2009Cross-sectionalHomeAll women with planned home birth (low risk pregnancies)MixedNS891.1Kongnyuy et al (2008)Cameroon (2004–2005)Cross-sectionalMedical facility (hospital)Singleton pregnancyPrimiparasMixed100311.6Saxena et al (2010)India (2007)CohortMedical facility (hospital)All vaginal deliveries during study periodPrimiparasMixed21067.60.95Moghadam et al (2015)…”
Section: Resultsmentioning
confidence: 99%
“…One randomized clinical trial has shown that the DSM‐A scale was validated by psychiatrists for effectiveness in screening for traumatic birth and compatibility with the definition of traumatic birth 34 . Moghadam et al 35 also confirmed the rationality and validity of this scale. However, in contrast with the DSM‐A scale, participants were only asked whether they would describe their birth as traumatic (yes/no) according to self‐reports 22,24,27 .…”
Section: Discussionmentioning
confidence: 97%
“…In a study by Soderquist et al, the PTSD prevalence across time points after childbirth was reported 0.9 -7.1% (28). In Iran, two studies performed in Zahedan reported the PSTD prevalence of 17.2 -32% (16,17). It was up to 36.7% in Bushehr (18) and 39% in the Southern West Azerbaijan Province (19).…”
Section: Discussionmentioning
confidence: 99%
“…It compromises 1 -3% of total childbirths in most European countries (England, Sweden, Germany, Italy) (5-11), 5.9% in Nigeria (12), 8 -9% in Canada and the US (13,14), and up to 13% in France (15). In Iranian settings, it is reported 17.2 -32% in two studies conducted in Zahedan (16,17), up to 36.7% in Bushehr (18), and 39% in Southern cities of West Azerbaijan Province (19), all higher than the global rate.…”
Section: Introductionmentioning
confidence: 99%